Comparison of Vertical Jump Test Measuring Instruments with Choronojump on the Explosive Power of Leg Muscles of Indonesian Badminton Elite Athletes - Iwan Hermawan; Fahmy Fachrezzy; Shela Ginanjar; Dena Widyawan; Fachri Husaini; Uzizatun Maslikah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research uses the Survey Research Method, a quantitative research type approach meaning research that is comparative or different. The population and sample in this study were 17 Indonesian Badminton Elite athletes consisting of male and female athletes. Data collection techniques using tests and measurements: physical condition tests; For leg muscle explosiveness by using a vertical jump measuring instrument and a chronojump. Data analysis using quantitative descriptive analysis techniques, overall data analysis using SPSS version 23. To obtain the results of this study, which is better the result of the explosive power of the leg muscles in Indonesian Badminton athletes using Vertical Jump and Chronojump. The results of this study showed that: There was a difference in the explosive power of the limbs in terms of the use of vertical jump and chronojump tools in  Indonesian Badminton Elite athletes with an average value between the two groups, whereas in the vertical jump group with an average value of  40.91,  the chronojump group with an average value of 45.47. This means that the chronojump group is better than the vertical jump group, this is evidenced by the results of descriptive analysis of the study with an average difference of 4.56. However, further research is recommended to pay attention to other physical factors, athlete psychology, and other factors that affect the achievements of elite Indonesian badminton athletes.